2015
DOI: 10.1681/asn.2013090961
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Effects of HPSE2 Mutations

Abstract: Urofacial syndrome (UFS) is an autosomal recessive congenital disease featuring grimacing and incomplete bladder emptying. Mutations of HPSE2, encoding heparanase 2, a heparanase 1 inhibitor, occur in UFS, but knowledge about the HPSE2 mutation spectrum is limited. Here, seven UFS kindreds with HPSE2 mutations are presented, including one with deleted asparagine 254, suggesting a role for this amino acid, which is conserved in vertebrate orthologs. HPSE2 mutations were absent in 23 nonneurogenic neurogenic bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 27 publications
10
69
1
Order By: Relevance
“…The nonsense mutation in HPSE2 gene of our patient has been formerly defined in two Turkish brothers (8). They both had large trabeculated bladder without VUR and one also had high Scr as in our patient.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The nonsense mutation in HPSE2 gene of our patient has been formerly defined in two Turkish brothers (8). They both had large trabeculated bladder without VUR and one also had high Scr as in our patient.…”
Section: Discussionsupporting
confidence: 59%
“…Some others proposed that two separate lesions affecting facial nerve nucleus and sacral cord motor nuclei innervating the external sphincter were responsible (6). The most recent studies in animal models indicate a peripheral autonomic neuropathy for BD in UFS (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these mutations may be responsible for other bladder diseases like NNNB or severe LUTD. Very recently, Stuart et al screened LRIG2 and HPSE2 mutations in 23 patients with NNNB and found potentially pathogenic variants in LRIG2 in only one case [17,24]. Likewise, in our study we did not find HPSE2 mutations in patients with NNNB and severe LUTD.…”
Section: Discussionsupporting
confidence: 54%
“…This congenital disorder features somatic motor neuropathy, obvious in the face but occasionally more widespread, and an autonomic neuropathy causing bladder dysfunction leading to renal failure (41). Notably, biallelic mutation in the HPSE2 gene is held responsible for some cases of UFS in families from different ethnic groups (4244), resulting in frameshift or nonsense, postulated functionally null, Hpa2 variants (45). Moreover, mice carrying mutant Hpa2 exhibit bladder dysfunction (44, 46), associating with increased bladder fibrosis (46).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, biallelic mutation in the HPSE2 gene is held responsible for some cases of UFS in families from different ethnic groups (4244), resulting in frameshift or nonsense, postulated functionally null, Hpa2 variants (45). Moreover, mice carrying mutant Hpa2 exhibit bladder dysfunction (44, 46), associating with increased bladder fibrosis (46). The relevance of our findings with Hpa2 over expressing head and neck carcinoma cells (i.e., increased cell differentiation, neurogenesis, LOX expression) to UFS and the lethality phenotype of Hpa2 mutant mice (46) are yet to be resolved.…”
Section: Discussionmentioning
confidence: 99%